An empire of light?: II: Learning and lawmaking in Germany today - Vogenauer, S (2006)
German law is commonly assumed to be strongly influenced by legal scholarship. This was certainly true in the past, and this article explores whether it is still the case today. But what is actually meant by 'influence' in the context of law? Who exerts it on whom, and how? These questions are analysed in the first part of the article. It is then shown, by drawing on biographical material, legislative history and case law, how legal scholarship contributes to both the legislative and the judicial lawmaking process in Germany - and where it does not. Finally it is asked how the specific relationship between legal academics and lawmakers in the German legal system can be explained and whether this model can be transferred to other systems. Copyright © 2006 Oxford University Press.